Tsunami damage assessment and monitoring of reconstruction in Nagapattinam area using multispectral images. (1st October 2016) - Jiji, G. Wiselin; Merlin, G. Sumilda
ABSTRACT: This paper presents a new remotely sensed solution for monitoring the recovery of a tsunami-affected area. Nagapattinam province of Tamilnadu, which was strongly attacked by the 2004 Indian Ocean tsunami, is selected as the demonstration site. IKONOS sets acquired on 10 June 2003 (pre-tsunami), 29 December 2004 (immediate-tsunami) and 31 October 2005 (post-tsunami) are used in this study. This proposed architecture worked in three tier architecture. In the first level, registration and removal of clouds are carried out. In the second level, object-based terminology is used to segment building, land, sand, vegetation and water. In the third level, change in the detection of object-based operation was performed. This method has given the solution for the building and infrastructural damages and monitoring of reconstruction work carried over the Nagapattinam area. The results proved that the proposed work has produced a higher accuracy assessment (99%). The change in detection results revealed a significant change in building after the tsunami as 25.5%, an increase in soil exposure as 21.4% and an increase in water within the soil and land as 8%, when the results are compared with the ground truth (GT). GT was obtained by manual analysis through field visits. The maximum sea water inundation distance of 486 m was observed in an Elancheran Nagar village which is located in the coastal Nagapattinam. We observed from the results that 18% of buildings were built by the government.